STUDY OF CONSUMER ACCEPTANCE ON THE NORI SEAWEED (Gracilaria sp.) WITH THE ADDITION OF NATURE DYES SUJI LEAVES Pleomele angustifolia - Sinaga, Pransiska; Mus, Sukirno; Suparmi, Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This aim of this research is to understand consumer acceptance on the nori seaweed (Gracilaria sp.), to understand how to making nori from Gracilaria sp. and to find resulting product.The method used experimental method, with Completely Randomized Design (CRD) non factorial with 4 levels treatment D0 (control), D1 (5%), D2 (10%) and D3 (15%). The result of this research showed the most like organoleptic by consumer that D3 treatment(15%) was the best treatment with characteristics: dark green color, the aroma of seaweed nori, crunchy texture,the flavors were salty with moisture value (10,46%), ash (25,81%), fat (1,23%),protein (10,45%),and fiber content (46,07%) Keywords: Gracilaria sp., Suji Leaves, Organoleptic, Proximate Parameters.